Information-Seeking Behaviour: Tuberculosis Health-Related Social Media Usage Among Generation Y In Malaysia - Harun, Sarina (2023)
This study examines the use of social media related to Tuberculosis (TB) health among Generation Y in Malaysia. Generation Y is the most active generation on social media. However, the search for health information on social media among Generation Y is decreasing, and Generation Y is the largest contributor to TB cases in Malaysia. Taking into account the Technology Acceptance Model (TAM), this study offers a more comprehensive theoretical perspective to understand the technological aspects contributing to literacy of perceived ease of use, and perceived usefulness of using social media related to TB health. In addition, perceived susceptibility and perceived severity regarding TB disease and cues to action from the Health Belief Model (HBM) also contribute to literacy in understanding health aspects. Moreover, this study provides a better understanding of the social aspects of Social Capital Theory (SCT), which elucidates the concept of social bonding and social bridging existing in social media. Furthermore, this study also explains the attitude concept from TAM as a mediator between perceived ease of use, perceived severity, cues to action, perceived usefulness, social bonding, and social bridging in the use of social media related to TB health. Four hundred and fifty respondents were involved in the online questionnaire survey to test hypotheses. The collected data were analysed using IBM Statistical Package for Social Science (SPSS) version 23 and Partial Least Squares-Structural Equation Modelling (PLS-SEM).